Proceedings of the 38th Annual Hawaii International Conference on System Sciences
DOI: 10.1109/hicss.2005.479
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Learning and Culture in the Managerial Implementation of Clinical e-Health Systems: An International Perspective

Abstract: When introducing a new technology that changes the core processes of an organization, such as an e-health initiative, it is important that the structural design and culture of the organization is aligned with the predominant national culture in which the organization is embedded. When a harmonious alignment is achieved, speedy and effective organizational learning can occur. This, in turn, promotes effective utilization of the new technology. The cultural dimension of uncertainty avoidance provides guidance on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…These organizational characteristics were our own modification, made after the initial pilot investigations (Stojkovic et al, 2009;Paunković et al, 2010), of the organizational characteristics found in the literature to correlate with culture and structure of organizations (Doktor et al, 2005). These organizational characteristics were our own modification, made after the initial pilot investigations (Stojkovic et al, 2009;Paunković et al, 2010), of the organizational characteristics found in the literature to correlate with culture and structure of organizations (Doktor et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These organizational characteristics were our own modification, made after the initial pilot investigations (Stojkovic et al, 2009;Paunković et al, 2010), of the organizational characteristics found in the literature to correlate with culture and structure of organizations (Doktor et al, 2005). These organizational characteristics were our own modification, made after the initial pilot investigations (Stojkovic et al, 2009;Paunković et al, 2010), of the organizational characteristics found in the literature to correlate with culture and structure of organizations (Doktor et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…This, in turn, promotes effective utilization of the new technology (Doktor et al, 2005). When a harmonious alignment is achieved, speedy and effective organizational learning can occur.…”
Section: Sustainable Utilization Of Ehealth Is Influenced By Organizamentioning
confidence: 98%
“…For the development of e-health, apart from the ICT infrastructure readiness, the acceptance of any information system requires proper planning and management for change in an organisational context (Calloni, 2006). It is also crucial when introducing a new technology that changes the core processes of an organization, such as an e-health initiative: it is important that the structural design and culture of the organization is aligned with the predominant national culture in which the organization is embedded (Doktor, 2005). Actually with electronic health records implementations, change occurs not simply due to the introduction of ICT infrastructure but also because the job design of interconnected health professionals should be reengineered to effectively and efficiently accomodate the technology (Ford, Menachemi, and Philips, 2006).Use of big data in digital health, especially implementation of electronic health records for a national health system has many advantages for the governments, guiding and planning the public health policies.…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Participants in the survey were asked to grade (1, not important; 5, very important) particular organizational characteristics. These organizational characteristics were found in the literature to correlate with organizational culture and structure (Doktor, Bangert & Valdez 2005 ).…”
Section: Research Objective and Study Designmentioning
confidence: 95%